INDEPENDENT WORK OF STUDENTS THROUGH THE INTERNET PEDAGOGICAL CONDITIONS OF ORGANIZATION - Yakubova Barno Bakhtiyarovna (Journals Park Publishing, 2022)
There was considered the requests of using of Internet and modern info communication technologies on organizing student’s independent works in this article. There was analyzed pedagogic conditions of organizing student’s independent work by Internet. The authors research the efficiency of using of info – communication technologies in this process.
Keywords: pedagogical conditions; modern info-communication technologies; student’s independent work